2020
DOI: 10.1093/hmg/ddaa172
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the [4Fe–4S] cluster of NFU1 requires the coordinated donation of two [2Fe–2S] clusters from the scaffold proteins, ISCU2 and ISCA1

Abstract: NFU1, a late acting iron–sulfur (Fe-S) cluster carrier protein, has a key role in the pathogenesis of the disease Multiple Mitochondrial Dysfunctions Syndrome (MMDS1). In this work, using genetic and biochemical approaches, we identified the initial scaffold protein, mitochondrial ISCU (ISCU2) and the secondary carrier, ISCA1, as the direct donors of Fe-S clusters to mitochondrial NFU1, which appears to dimerize and reductively mediate formation of a bridging [4Fe-4S] cluster, aided by ferredoxin 2 (FDX2). By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 55 publications
5
29
0
Order By: Relevance
“…Most of the nfu-1 mutations resulted in impaired delivery of lipoic acid to PDH and KGDH (Fig 1D and 1E) as has also been observed in MMDS1 samples [16,19], patient-derived fibroblasts [11,15,17,19,21,28,40], and NFU1 mutant rodents [41], plants [42], and yeast [8]. A single mutant, Arg140Gln appears unaffected in its ability to lipoylate PDH and KDGH.…”
Section: Nfu-1/lpd-8 Is Orthologous To Nfu1supporting
confidence: 65%
See 2 more Smart Citations
“…Most of the nfu-1 mutations resulted in impaired delivery of lipoic acid to PDH and KGDH (Fig 1D and 1E) as has also been observed in MMDS1 samples [16,19], patient-derived fibroblasts [11,15,17,19,21,28,40], and NFU1 mutant rodents [41], plants [42], and yeast [8]. A single mutant, Arg140Gln appears unaffected in its ability to lipoylate PDH and KDGH.…”
Section: Nfu-1/lpd-8 Is Orthologous To Nfu1supporting
confidence: 65%
“…This information, paired with the data herein about diffences between alleles, suggests that the amino acid changes are likely the causes of dysfunction rather than reduced NFU-1 protein abundance. Second, recent work has demonstrated that the C-terminus of NFU1, including residues surrounding the ISC-binding motif is important for interactions with both other members of the ISC biogenesis machinery and NFU1 targets [9,11]. We cannot exclude the possibility that the modeled nfu-1 mutants also disrupt those types of interactions and likewise alter ISC handling.…”
Section: Nfu-1 Mutations and Impaired Isc Handlingmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been proposed, on the basis of a combination of in vitro and in vivo studies [ 23 , 28 ], that the BOLA3–GLRX5 complex transfers its [2Fe–2S] 2+ cluster to protein partners, such as NFU1 [ 26 ], which are involved in the final steps of the maturation of mitochondrial [4Fe–4S] cluster-binding target proteins [ 28 , 58 ]. On this respect, it is also relevant to investigate how the Cys59Tyr mutation affects the Fe–S cluster-binding properties of the hetero-complex, as Cys59 is a ligand of the [2Fe–2S] 2+ cluster in the hetero-complex [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like ISCA1/2, the mitochondrial [4Fe-4S] cluster protein, NFU1, helps assemble and facilitate intramitochondrial [4Fe-4S] trafficking. The [4Fe-4S] 2+ ISCA1/2 heterodimer can directly transfer the cluster to NFU1 ( Figure 3 A) [ 66 ]. Holo-ISCA1 and holo-ISCU can also bind directly to NFU1 to donate a [2Fe-2S] cluster for [4Fe-4S] cluster formation in an FDX2 dependent manner ( Figure 3 B) [ 67 ].…”
Section: Overview Of Fe–s Biogenesismentioning
confidence: 99%